Transforming Population Administration Services in Indonesia for Enhanced Excellence - A’yuningsih, Zumrotul; Rodiyah, Isnaini (Indonesian Journal of Cultural and Community Development, 2024)
General Background: The quality of public services, particularly in population administration, is crucial for effective governance and community satisfaction. Specific Background: This research investigates the quality of Population Administration Services using the Plavon Dukcapil Application in Dukuhsari Village, Jabon Sub-district, Sidoarjo Regency, highlighting the importance of technology in enhancing administrative efficiency. Knowledge Gap: Despite the implementation of digital solutions like Dukcapil Plavon, there is limited understanding of how these applications affect service quality from the perspective of both government officials and the community. Aims: This study employs a descriptive qualitative method, utilizing observation and interviews to analyze service quality based on five dimensions: tangibles, reliability, responsiveness, assurance, and empathy. Results: Findings reveal that the Dukuhsari Village government has established adequate physical infrastructure and consistently meets residents' needs through timely and polite services. The village employees demonstrate responsiveness by providing clear information regarding service processes, while empathy is evident in their attentive approach to residents’ administrative needs. The study indicates that, although services are generally satisfactory, there is room for improvement in ensuring that all staff members are consistently trained in using the Plavon Dukcapil Application. Novelty: This research contributes to the existing literature by examining the interplay between digital applications and service quality in local governance, offering empirical insights into the effectiveness of the Dukcapil Plavon system. Implications: The study underscores the necessity for ongoing training and support for village officials to enhance service delivery further and ensure equitable access to population administration services for all residents. Highlights: Infrastructure: Adequate facilities support effective population administration services. Responsiveness: Timely information provided to residents about administrative processes. Empathy: Caring staff ensure equitable service delivery without discrimination. Keywords: Population Administration, Dukcapil Plavon, Service Quality, Qualitative Research, Local Governance